PENGEMBANGAN KURIKULUM PENDIDIKAN INKLUSI BERBASIS DIFERENSIASI DI SEKOLAH DASAR - Dina Trisia; Septi Fitri Meilana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of an inclusive education curriculum based on differentiation is a strategic step to meet the diverse needs of students, especially in elementary schools. This article aims to analyze and elaborate on the concept, implementation, and challenges of an inclusive curriculum combined with a differentiation approach. The research uses a literature review method by analyzing various sources of SINTA-indexed journals, books, and related guidelines from the past five to ten years. The study results indicate that inclusive education in elementary schools often faces challenges in designing a curriculum that can accommodate the individual needs of students, especially those with special needs. The differentiation approach offers a solution that enables flexible, adaptive, and student-centered teaching. This strategy includes differentiation of content, process, product, and learning environment tailored to the abilities and learning styles of students. In addition, strong collaboration between teachers, parents, and stakeholders is needed to ensure the successful implementation of this curriculum. This article recommends the development of training programs for teachers to understand and implement differentiation approaches, as well as the integration of technology to support inclusive learning. Thus, a differentiation-based inclusive curriculum can serve as an important foundation in creating an inclusive, adaptive, and diversity-supporting learning environment for students.